Relativism and Alethic Functionalism - Zeman, Dan (Organon F, 2007)
The essay is an attempt to offer a version of conceptual relativism that escapes Donald Davidson’s (widely thought) decisive criticisms of the notion of “conceptual scheme”. Two variants of relativism are distinguished, a weaker and a stronger one, and a clear formulation of what a strong version amounts to is put forward. The concrete proposal involves accepting a version of alethic pluralism. After discussing alethic pluralism in general, and after exploring both strong and weak versions of it, a suitable version is presented: alethic functionalism. The final part offers an illustration of how embracing alethic functionalism may help the relativist.